The impact of green technology innovation on global value chain upgrading in China’s equipment manufacturing industry - Li, Yan; Zhang, Xiaohan; Hao, Jinyun; Huang, Qingbo (Frontiers in Environmental Science, 2022)
China’s equipment manufacturing industry is actively embedding in global value chain (GVC), but pollution emission has become an important factor restricting the industry from climbing to the high-end link of GVC. Chinese government and enterprises urgently need to solve this problem through green technology innovation. In recent years, the effect of green technology innovation has attracted extensive attention from scholars, but existing studies have not discussed whether and how green technology innovation can promote GVC upgrading. Thus, this study examines the impact of green technology innovation on GVC upgrading using data of China’s equipment manufacturing industry from 2007 to 2019. The results show that for the full samples, there is a U-shaped relationship between green technology innovation and the promotion of GVC status; and for upstream leading sectors, the conclusion is same with the whole industry; but for mixed leading sectors, the trend is opposite, that is, an inverted U-shaped relationship of first rise and then decline. Additionally, green technology innovation in China’s equipment manufacturing industry can exert a positive influence on GVC upgrading by reducing its dependence on GVC, optimizing export trade, reducing pollution costs, and promoting green product and process innovation. Therefore, the Chinese government should strengthen the environmental regulation policy to force enterprises to carry out green technology innovation; improve the market supply system for factors of production and increase the training of green and innovative personnel; promote the green innovation-driven development strategy, pushing the industry from “factor driven” to “green innovation-driven”.